1976
DOI: 10.1073/pnas.73.12.4546
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the induction of colonies in vitro by normal human lymphocytes.

Abstract: Lymphocytes isolated from normal human peripheral blood can be induced to form colonies in vitro by incubation with the appropriate inducer. Phytohemagglutinin can induce colonies with T (thymus-derived) lymphocytes. Optimum colony formation with about two colonies per 102 peripheral blood lymphocytes was obtained by adding, in addition to phytohemagglutinin, autologous plasma, autologous red blood cells, and fresh L-glutamine or L-cystine. In the absence of these fresh amino acids, no colonies were formed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1977
1977
1996
1996

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Another possibility is that lipopolysaccharide (endotoxin) may be present in CM and cause formation of colonies. This seems unlikely since the mitogenic effect apears to be exerted predominantly on B cells (15), and recent experiments have shown that although lipopolysaccharide potentiated the colony-inducing activity of mitogenic factors such as PHA, it did not induce colony formation de novo (16). Furthermore the cell lines used in this study were free from bacterial contamination, and the CM did not contain endotoxin as judged by the limulus assay (17).…”
Section: Discussionmentioning
confidence: 86%
“…Another possibility is that lipopolysaccharide (endotoxin) may be present in CM and cause formation of colonies. This seems unlikely since the mitogenic effect apears to be exerted predominantly on B cells (15), and recent experiments have shown that although lipopolysaccharide potentiated the colony-inducing activity of mitogenic factors such as PHA, it did not induce colony formation de novo (16). Furthermore the cell lines used in this study were free from bacterial contamination, and the CM did not contain endotoxin as judged by the limulus assay (17).…”
Section: Discussionmentioning
confidence: 86%
“…The presence of erythrocytes in the culture system may contribute to the enhanced growth of colonies from WB. Addition of RBC [9,13,14] or RBC membrane preparations [I51 to lymphocyte cultures has been previously reported to potentiate T lymphocyte colony formation. It is possible that soluble mediators or membrane interactions may be responsible for this enhancement.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that human lympho cytes can be induced to form colonies in semisolid culture media [8,11,20]. T cell colony formation in agar culture has been thus evaluated under various experimental conditions [2,12,19,21], and is currently investigated in several hematological diseas es [3,5,6,9,10,16].…”
Section: Introductionmentioning
confidence: 99%